Neo-Calvinism. A Theological Introduction Cory C. Brock and N. Gray Sutanto: Bellingham: Lexham Academic, 2022; xxii + 322 pp, £20.69, hb; ISBN 9781683596462 - McGowan, Andrew T. B. (European journal of theology, 2025)
The purpose of this book is to provide a theological account of neo-Calvinism, as drawn from the writings of its founders, Abraham Kuyper and Herman Bavinck. Their development of an organic as opposed to a mechanical understanding of theology helps us to avoid various pitfalls. Rooted in Calvin, they sought to learn from the non-Calvinist theologies of their day. On key subjects such as natural theology, general revelation, Scripture, common grace and theological anthropology, they developed a nuanced theology which is well described in this excellent book.